The history of the brain and mind sciences : technique, technology, therapy - Casper, Stephen T.; Gavrus, Delia (Rochester studies in medical history., 2017)
How did technicians, epidemics, zoos, German exiles, methamphetamine, disgruntled technicians, modern bureaucracy, museums, and whipping cream shape the emergence of modern neuroscience?